Influência da dose infectante na colonização bacteriana do sistema de canais radiculares e na translocação para linfonodos submandibulares em camundongos gnotobióticos - Sandra Maria de Melo Maltos (2001)
The aim of the endodontic therapy is to reduce the number of viable bacteria present in the infected root canal system (RCS) by means of a chemo-mechanical preparation. It is believed that although complete sterilization is not reached after this procedure, the number of remaining microorganisms is not enough to recolonize the RCS.The purpose of this study was to establish the concentration of E. faecalis (ATCC 4083) and P. nigrescens (ATCC 33563) able to implant in the root canal system (RCS) of germ-free (GF) mice and translocate to the submandibular lymph node (SML).Seventy-two one-month-old germ-free mice, both male and female, whose lower central incisive canal was instrumented and inoculated with E. faecalis at 102 and 101 UFC concentrations or P. nigrescens at 105, 104, 103 102 UFC concentrations and sealed.The results have demonstrated that E. faecalis implanted, in 83,33% of the cases, at 102 and 101 UFC concentrations. Translocation has occurred in 58.33%, for the 102 UFC inoculum, and in 33.33% for the 101 UFC inoculum. P. nigrescens implanted in 25%, 16.67%, 8.33% and 0%, for the 105, 104, 103 and 102 UFC inocula, respectively. The translocation phenomenon has not been observed at any concentration used for the mentioned species. These results allow us to conclude that E. faecalis was able to implant in the RCS and translocate to the SML, even in concentrations considered low, while P. nigrescens implanted in small percentages in the RCS, and was not able to translocate to the SML in this experimental model.